Evaluation of the influence of the turning radius of heavy vehicles inside a roundabout in vehicular conflicts - Luna, Cesar Oswaldo Vera (2023)
Roundabouts allow a continuous vehicular flow and a greater traffic capacity compared to conventional intersections. This alternative makes it possible to improve the critical situation at some points on the main roads. However, its efficiency is reduced when the structure has a reduced area. Likewise, the presence of heavy vehicles affects the continuous circulation of other vehicles because they occupy more than one lane to make the turn correctly. Therefore, there are many vehicle conflicts, delays and queues. This research aims to evaluate conflicts in a roundabout with a reduced area. Then, in scenario 1, the heavy vehicles in the roundabout under study were replaced by cars to evaluate the influence of heavy vehicles through the variation of vehicular conflicts. Finally, compare a second scenario of a roundabout with defined lanes for heavy vehicles inside the central island. The defined lanes that cross the central island have a greater turning radius compared to those designed in the roundabout. Data collection of the current situation was performed and then Vissim microscopic simulation software was used to simulate the scenarios using the collected traffic data. To evaluate the turning radius, the design vehicle used was the semi-Trailer (trailer), since it is one of the main ones that circulates through the intersection under study and requires a wide turning radius. The results of scenario 1 that replaces the trailers with cars show a decrease in conflicts by 20%. In the same way, it happens in scenario 2, which presents a similar reduction in vehicular conflicts than scenario 1. Likewise, scenario 2 presents a decrease in vehicular delays, which improves the efficiency of the infrastructure under study.